FENOMENA ESTRUS DOMBA BETINA LOKAL PALU YANG DIBERI PERLAKUAN HORMON FSH - Ridwan Ridwan (Universitas Tadulako, 2006)
The research aims to know and give information regarding effect of FSH hormone to estrus phenomena of ewe local Palu. The research use 8 ewe local Palu and 2 local Palu sheep as stud, which is divided into 2 groups, the group with treatment of FSH hormone and the group without treatment of FSH hormone. Qualitative data obtained in this research has been analyzed by using descriptive method. Quantitative data has been statistically analyzed by using T test. The statistics results shows that both sheep groups with treatment of FSH hormone and without treatment of FSH hormone have significant effect (P<0,05) towards estrus period. However, estrus performance of sheep with treatment of FSH hormone is higher than sheep without treatment of FSH hormone.